Interleukin 18, soluble cluster of differentiation 40, platelet factor 4 variant 1, and neutrophil gelatinase-associated lipocalin can be used as biomarkers to aid activity and diagnosis in ocular Behcet's disease - Celik, Fatih; Coteli, Ebru; Gul, Fatih Cem; Ozsoy, Ercan; Kobat, Sabiha Gungor; Karagoz, Zuhal Karaca; Aydin, Suleyman (Springer, 2022)
Purpose The molecules human interleukin (IL-18), the soluble cluster of differentiation (sCD40), platelet factor 4 variant 1 (PF4V1), and neutrophil gelatinase-associated lipocalin (NGAL) are all markers of inflammation in biological systems and are linked to prognosis in several inflammatory diseases as well. Since there is no study in which the above-mentioned molecules are studied together in ocular Behcet's disease (OBD), the aim of this study is to reveal whether these molecules are activity markers in active (OABD) and inactive (OIBD) disease. Methods 30 OABD and 30 OIBD and 30 healthy individuals were included in the study. IL-18, sCD40, PF4V1, and NGAL molecules were studied in blood samples by the ELISA method. Results When OABD and OIBD were compared to healthy individuals, the levels of IL-18, sCD40, PF4V1, and NGAL molecules were found to be statistically significant. These values were even more significantly higher in patients with OABD. Conclusion When ROC values of IL-18, sCD40, PF4V1, and NGAL are evaluated, it is clear that these four molecules can be used as biomarkers to aid activity and diagnosis in OBD.
Keywords: Interleukin; Neutrophil gelatinase-associated lipocalin; Ocular Behcet's disease; Platelet factor; Soluble cluster of differentiation